The effects of emotion on self-regulation - Low, Yi Hua (2015)
Different types of emotions have been found to differentially influence our cognition, thoughts and behaviors. However, despite the rich literature, emotions are largely studied as outcomes of self-regulation, and the possibility of emotions inducing self- regulatory focus orientations remains largely unexplored. In this study, we hypothesized that experiencing positive emotions can cause individuals to adopt a promotion focus and experiencing negative emotions can cause an individual to adopt a prevention focus. We examine this prediction in an individual via two ways—an individual’s chronic self-regulation, and also temporarily induced self-regulation. In examining chronic self-regulation, we explored the mediating effect of type of emotion chronically experienced, between personality traits and self-regulation. In examining temporary self-regulation, we explored whether a momentary experience of positive or negative emotion can foster a promotion or prevention focus respectively. In this study we found that positive emotion indeed fosters a temporary promotion focus and negative emotion can foster a temporary prevention focus. However, our mediation hypothesis on chronic self-regulation was not supported. While emotions are often studied as an outcome of self-regulation, our results suggest that emotions could instead be a precursor to self-regulatory orientations, and future studies could expand the investigation of chronic self-regulatory foci by considering the influence of emotions.